Injury prevention strategies in dance: a systematic review - Critchley, M. L.; Rio, E.; Friesen, K. B.; Räisänen, A. M.; Kenny, S. J.; Emery, C. A. (Journal of Dance Medicine & Science, 2025)
Background: Dance is a popular activity worldwide that comes with inherently high injury rates. Despite the call for implementation and evaluation of injury prevention strategies, the utility and efficacy of injury prevention practices in dance are unknown.